Efektivitas Strategi Transformasi Radio Republik Indonesia dalam Menarik Minat Generasi Z di D.I. Yogyakarta - Wulandari, Yuni; Oloan, Jordan; Saintera, Nadialala Josepika; Wahyudin, Ade (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2025)
This study analyzes the effectiveness of Radio Republik Indonesia's (RRI) digital transformation strategy in attracting Generation Z audiences in Yogyakarta Special Region. Using a quantitative descriptive approach based on a survey of 124 respondents, the research evaluates audience perceptions, media consumption habits, and expectations toward RRI's digital services. Findings indicate that RRI has adopted digital innovations like live streaming, podcasts, and social media content distribution. Yet, audience awareness remains moderate (mean 3.34), while preferences for digital channels and podcasts are high (mean 3.84 and 3.98). The main barriers include the dominance of alternative media (77.4%) and limited promotion (47.6%). Nevertheless, Generation Z shows strong interest in interactive content (67.7%) and expects RRI to be more active on digital platforms. The study concludes that RRI’s digital transformation is progressing in the right direction but requires improved visibility, content quality, and interactivity through social-first distribution and content-value redesign strategies to better align with Generation Z's media consumption patterns